Enhancing Students’ Soft Skills Through Digital Literacy Integration in Islamic Education: A TPACK-Based Approach - Afnan, Haidar; Maksum, Muhammad Nur Rochim (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to describe the effectiveness of digital literacy skills in enhancing soft skills in Islamic Religious Education (PAI) learning and to identify the supporting and inhibiting factors in its implementation. Using the TPACK approach (Technology, Pedagogy, and Content Knowledge), this research integrates technology, pedagogy, and content knowledge into the learning process. Digital literacy is considered essential in developing students’ soft skills, such as communication, discipline, ethics, and social abilities. The research method is qualitative, with field research conducted at SMP Muhammadiyah 5 Surakarta using a phenomenological approach. Data were collected through observation, interviews with the PAI subject teachers and the students, and documentation. Data analysis involved reduction, data presentation, and verification using source and technique triangulation. The findings show that the implementation of the TPACK approach in PAI learning improves students’ digital literacy, which positively impacts their soft skill development. However, challenges include limited access to technology, lack of technical support, and teacher resistance to change. The study emphasizes that effective application of digital literacy can enhance teachers’ pedagogical competence and professionalism, supporting more interactive and innovative learning. Therefore, infrastructure support and teacher training in technology use are needed to optimize PAI learning in the digital era.